Designing course materials for Quranic Language 1: towards promoting student-centred learning culture in IIUM based on TBLT approach - Jaafar, Nor Azlina; Muhammad, Norasmazura; Ahmad, Nor Syahida; Omar, Haliza Maimuna; Hashim, Marzidah; Raja Sulaiman, Raja Munirah; Mohd Nor, Manisah (2014)
Task-based language teaching (TBLT) is not a common approach in teaching Arabic for non-native speakers in Malaysia. Prior to 2012, teachers of Arabic language courses in CELPAD mostly used the traditional method in their teaching. Students relied totally on their teachers: from explaining the subject, translating the text, preparing the exercises until choosing groups of vocabulary that they must memorize. TBLT is implemented by CELPAD to produce IIUM graduates who are able to use basic Arabic language vocabulary in their conversation even though they are not majoring in Arabic-based programs. By introducing this new approach in CELPAD, it has created major changes in the teaching of Arabic language in IIUM. Students have to adapt to a totally different approach as compared to whatever they were accustomed to in their secondary school. Outside the Arabic speaking world, particularly in Malaysia, there are hardly any other institutions that employ such approach in Arabic language teaching. Therefore, this project is conducted to assist teachers of Arabic language in IIUM to adopt this new approach in their teaching process.